THE EFFECTIVENESS OF PICTURE AND PICTURE LEARNING MODELS ON THE SKILLS OF WRITING NARRATIVE PAPERS - Sangadah, Kuni; Purwanti, Eko; Abidin, Zaenal; Sismulyasih, Nugraheti (Elementary School Teacher, 2020)
Based on the result of interview and observation it was known that the Indonesian language learning outcomes on essay writing the topic were low because the teachers still used the lecture method in learning process. This research aimed to test the effectiveness of the picture and picture learning model on essay writing skills of the students in Mijen District Elementary School, Semarang City. This research used quantitative method with the type of experimental research. This research design was quasi experimental design in the form of nonequivalent pretest-posttest design. The sample technique used was cluster random sampling in the number of 57 students. The data collection techniques used were interviews, observation, documentation, and performance tests. The results showed that the experimental class posttest results were higher than the control class and included in good categories. That means the picture and picture learning model was effective to be used on essay writing skills topic. The n-gain test results showed that the experimental class obtained a higher increase in the amount of 0.32 in the medium category and the control class was in the amount of 0.12 in the low category. The conclusion of this research is a picture and picture learning model was effective to be used on essay writing skills topic in Mijen District Elementary School, Semarang City. The n-gain test results showed that the experimental class obtained a higher increase in the amount of 0.32 in the medium category and the control class was in the amount of 0.12 in the low category. The conclusion of this research is a picture and picture learning model was effective to be used on essay writing skills topic in Mijen District Elementary School, Semarang City. The n-gain test results showed that the experimental class obtained a higher increase in the amount of 0.32 in the medium category and the control class was in the amount of 0.12 in the low category. The conclusion of this research is a picture and picture learning model was effective to be used on essay writing skills topic in Mijen District Elementary School, Semarang City.